2021
DOI: 10.1590/1678-4685-gmb-2021-0084
|View full text |Cite
|
Sign up to set email alerts
|

Meiotic self-pairing of the Psalidodon (Characiformes, Characidae) iso-B chromosome: A successful perpetuation mechanism

Abstract: B chromosomes are non-essential additional genomic elements present in several animal and plant species. In fishes, species of the genus Psalidodon (Characiformes, Characidae) harbor great karyotype diversity, and multiple populations carry different types of non-essential B chromosomes. This study analyzed how the dispensable supernumerary B chromosome of Psalidodon paranae behaves during meiosis to overcome checkpoints and express its own meiosis-specific genes. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 58 publications
1
9
0
Order By: Relevance
“…Furthermore, in an extensive analysis based on satellite DNA mining by NGS and bioinformatics, Silva et al [ 46 ] revealed the presence of 14 families of satDNA clustered in BM and distributed symmetrically. All repetitive DNA mapped in this B chromosome suggested that the B chromosome of P. paranae is also an isochromosome, which was later confirmed by meiotic studies showing their self-pairing [ 39 ], as revealed in the B chromosome of P. scabripinnis [ 38 ]. The higher content of repetitive DNAs in this B chromosome than in standard chromosomes constitutes the different heterochromatin patterns between them [ 45 ], indicating that B chromosomes follow their own evolutionary pathway.…”
Section: Structure Of B Chromosomesmentioning
confidence: 83%
See 4 more Smart Citations
“…Furthermore, in an extensive analysis based on satellite DNA mining by NGS and bioinformatics, Silva et al [ 46 ] revealed the presence of 14 families of satDNA clustered in BM and distributed symmetrically. All repetitive DNA mapped in this B chromosome suggested that the B chromosome of P. paranae is also an isochromosome, which was later confirmed by meiotic studies showing their self-pairing [ 39 ], as revealed in the B chromosome of P. scabripinnis [ 38 ]. The higher content of repetitive DNAs in this B chromosome than in standard chromosomes constitutes the different heterochromatin patterns between them [ 45 ], indicating that B chromosomes follow their own evolutionary pathway.…”
Section: Structure Of B Chromosomesmentioning
confidence: 83%
“…Recent studies performed on Psalidodon indicated differential gene expression in individuals carrying B chromosomes [ 21 , 39 , 40 , 74 ]. A transcriptome analysis showed a high expression of two paralog genes on the B chromosome related to the cell cycle ( nobox and msh4 ) in females [ 21 ].…”
Section: Expression and Effects Of B-genesmentioning
confidence: 99%
See 3 more Smart Citations